2006
DOI: 10.1159/000088851
|View full text |Cite
|
Sign up to set email alerts
|

An Evoked Potential Study of the Developmental Time Course of the Auditory Nerve and Brainstem in Children Using Cochlear Implants

Abstract: Central auditory responses to electrical stimulation from a cochlear implant were studied in 75 pre-lingually deafened children and 11 adults. Electrically evoked auditory brainstem response (EABR) latencies significantly decreased with duration of cochlear implant use and were not significantly affected by the age at implant activation. Significant decreases in early latency waves and interwaves occurred within the first 1–2 months of implant use, whereas longer term changes (6–12 months) were found for eV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
87
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 72 publications
14
87
1
2
Order By: Relevance
“…Brainstem responses rapidly change over the first year of unilateral CI use in children with early-onset deafness. 118,119 When the opposite (second) ear was implanted after this period (.1.5 years), the brainstem responses from this ear remained abnormally prolonged despite up to 3 years of bilateral implant use (Fig 3 120,121 ). By contrast, bilateral implantation with minimal or no delay in early development promoted symmetric maturation of the responses for both ears.…”
mentioning
confidence: 96%
“…Brainstem responses rapidly change over the first year of unilateral CI use in children with early-onset deafness. 118,119 When the opposite (second) ear was implanted after this period (.1.5 years), the brainstem responses from this ear remained abnormally prolonged despite up to 3 years of bilateral implant use (Fig 3 120,121 ). By contrast, bilateral implantation with minimal or no delay in early development promoted symmetric maturation of the responses for both ears.…”
mentioning
confidence: 96%
“…well as development of the auditory brainstem [Gordon et al, 2003[Gordon et al, , 2006[Gordon et al, , 2007a and cortex [Gordon et al, 2005a, b]. Although there are benefits to using one CI, it has become clear that the immature auditory system requires input from both ears.…”
mentioning
confidence: 99%
“…23,24 Dees et al 25 and Gordon et al 21,12 have reported similar results. According to Haenggeli et al 26 and Miller et al, 27 direct stimulation of auditory neurons, by compensating synaptic mechanisms among cochlear hair cells and neural structures, partly explain the fact that ECAP latency is minimally affected by variations in the level of the current.…”
Section: N1 Peak Latencymentioning
confidence: 66%
“…[5][6][7] Studies in humans have shown different results in the stabilization of ECAP features, especially its amplitude, extrapolated threshold (p-NRT) and the amplitude growth curve slope. [8][9][10][11][12] Given the recent and significant technological developments in cochlear implant manufacturing, and continuous improvements in audiological diagnostic techniques, the indication criteria for cochlear implant have been extended to younger children. In the literature children with implants at age four months have already been reported.…”
Section: Introductionmentioning
confidence: 99%